Transforming a Traditional Home Gateway into a Hardware-accelerated SDN Switch - Sebastiano Miano; Fulvio Risso (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Nowadays, traditional home gateways must support increasingly complex applications while keeping their cost reasonably low.Software Defined Networking (SDN) would simplify the management of those devices, but such an approach is typically reserved for new hardware devices, specifically engineered for this paradigm.As a consequence, typical SDN-based home gateway performs the switching in software, resulting in non-negligible performance degradation.In this paper, we provide our experience and findings of adding the OpenFlow support into a non-OpenFlow compatible home gateway, exploiting the possible hardware speedup available in the existing platform.We present our solution that transparently offloads a portion of the OpenFlow rule into the hardware, while keeping the remaining ones in software, being able to support the presence of multiple hardware tables with a different set of features.Moreover, we illustrate the design choices used to implement the functionalities required by the OpenFlow protocol (e.g., packet-in, packet-out messages) and finally, we evaluate the resulting architecture, showing the significant advantage in terms of performance that can be achieved by exploiting the underlying hardware, while maintaining an SDN-type ability to program and to instantiate desired network operations from a central controller.